Dye degradation, antimicrobial activity, and molecular docking analysis of carbon sphere and graphene oxide–doped aluminum oxide - Hafiz Muhammad Zubair Arshad; Muhammad Imran; Ali Haider; Iram Shahzadi; Muhammad Mustajab; Anwar Ul-Hamid; Walid Nabgan; Francisco Medina; Sadaf Aslam; Muhammad Ikram (Frontiers in Environmental Science, 2023)
In this research work, pristine and various concentrations (2.4 wt%) of graphene oxide (GO)/carbon sphere (CS)–doped Al2O3 nanostructures (NSs) were synthesized with the chemical sol–gel method. Aluminum oxide (Al2O3) exhibits quick recombination of electrons and holes with a low specific surface to limit catalytic and antibacterial activities. Al2O3 doped with CS is good in wastewater treatment and reduces the size of NSs. The incorporation of graphene oxide (GO) into Al2O3 at different concentrations (2 and 4 wt%) enhances both the structural and chemical stabilities of the resulting material while concurrently decreasing the number of charge carriers and reducing the band gap energy. This modified Al2O3-GO composite exhibits promising potential for utilization in dye degradation and antibacterial activity. A series of characterizations were performed to investigate the structural, morphological, and optical properties. The NSs exhibited excellent catalytic activity (CA) against rhodamine B (RhB) dye in acidic, basic, and neutral media. The antimicrobial activity was tested against Escherichia coli. Pairs of electrons and holes are the primary building blocks for the production of reactive oxygen species (ROS), which causes bacteria to die. The significant inhibition zones against E. coli were calculated to be approximately 5.65 mm when compared to ciprofloxacin. Moreover, in silico investigations have revealed the possible inhibitory impact of produced nanomaterials (GO/CS-doped Al2O3) on DNA gyrase and FabI enzymes of fatty acid biosynthesis.